2021
DOI: 10.1108/jeas-05-2020-0077
|View full text |Cite
|
Sign up to set email alerts
|

The USA–China trade policy uncertainty and inference for the major global south indexes

Abstract: PurposeThe recent dynamics of trade policy, especially that is associated with the United States of America (USA) and China, has not only triggered policy adjustments in two economies, it has also implied an uncertainty spillover to other economies across the globe. Consequently, the current study attempts to examine the effect of uncertainties in the USA–China trade policies on stock market indexes. In addition, the cointegration evidence between the USA–China trade policy uncertainty index and of the leading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
0
7
1
Order By: Relevance
“…These results are consistent with recent studies that documented similar findings (Babarinde, 2020; Onali, 2020), who found that the performance of stock markets in the US and other COVID-19 highly ravaged economies were not impacted by movements in the number of cases and fatalities in the first three months of 2020, except for the log of a number of documented cases in China. However, these results are inconsistent with other recent studies that validated the significant sensitivity of the stock market to the novel coronavirus (Abu et al , 2021; Ashraf, 2020; Takyi and Bentum-Ennin, 2020; Goodell, 2020; Sharif et al , 2020; Salisu et al , 2020; Akdag et al , 2021; Kumeka et al , 2021; Raifu et al , 2021). For example, Takyi and Bentum-Ennin (2020) reported that following the incidence of Coronavirus, the performance of stock markets in Africa dropped by around negative 2.7% to 21%.…”
Section: Resultscontrasting
confidence: 98%
See 2 more Smart Citations
“…These results are consistent with recent studies that documented similar findings (Babarinde, 2020; Onali, 2020), who found that the performance of stock markets in the US and other COVID-19 highly ravaged economies were not impacted by movements in the number of cases and fatalities in the first three months of 2020, except for the log of a number of documented cases in China. However, these results are inconsistent with other recent studies that validated the significant sensitivity of the stock market to the novel coronavirus (Abu et al , 2021; Ashraf, 2020; Takyi and Bentum-Ennin, 2020; Goodell, 2020; Sharif et al , 2020; Salisu et al , 2020; Akdag et al , 2021; Kumeka et al , 2021; Raifu et al , 2021). For example, Takyi and Bentum-Ennin (2020) reported that following the incidence of Coronavirus, the performance of stock markets in Africa dropped by around negative 2.7% to 21%.…”
Section: Resultscontrasting
confidence: 98%
“…For example, Takyi and Bentum-Ennin (2020) reported that following the incidence of Coronavirus, the performance of stock markets in Africa dropped by around negative 2.7% to 21%. And Akdag et al (2021) also documented that the USA -China trade war significantly influenced the stock market indices of the sampled economies.…”
Section: Granger Causality Testmentioning
confidence: 93%
See 1 more Smart Citation
“…Just like the production of essential goods and services are subject to human needs, the prices of essential commodities are largely associated with the dynamics of their supply and demand. İn essence, the availability and/or prices of the essential goods and services are associated with the dynamics related to economic uncertainties, natural events or disasters and market-related factors (Balcilar et al ., 2016; Alola et al ., 2019; Akadiri et al ., 2020; Onifade et al ., 2020; Akdag et al ., 2021). Moreover, the monetary policies applied to one of the currency pairs or the macroeconomic consequences that may affect the currency, thus shaping the price trend of the currency pair.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary, remittances could increase the demand for goods that put more pressure on the local environment(L opez-Feldman & Chávez, 2017). On the other hand, several papers attempted to answer whether natural resources are a curse or blessing for the financial sector in terms of stability or development of the financial sector(Dwumfour & Ntow-Gyamfi, 2018;Akdag et al, 2021). Finally, additional macroeconomic variables are employed as control variables.…”
mentioning
confidence: 99%